Непертурбативна ангармонiчна поправка до формули мехлера для пропагатора гармонiйного осцилятора - Boh´acik, J.; August´in, P.; Presnajder, P. (Publishing house "Academperiodika", 2018)
We find the possibility of a non-perturbative anharmonic correction to Mehler’s formula for the propagator of a harmonic oscillator. The conditional Wiener measure functional integral with a fourth-order term in the exponent is evaluated using a method alternative to the conventional perturbative approach. In contrast to the conventional perturbation theory, we expand the term linear in the integration variable in the exponent into a power series. The case where thestarting point of the propagator is zero is discussed. The results are presented in analytical form for positive and negative frequencies.